Effects of news sowing arrangements and air assistance on fungicide spray distribution on soybean crop - Souza, Diego Miranda de [UNESP]; Raetano, Carlos Gilberto [UNESP]; Ferreira Moreira, Caio Alexandre [UNESP]; Oliveira de Freitas Bueno, Regiane Cristina [UNESP]; Carvalho, Marina Mouzinho [UNESP] (Univ Estadual Maringa, Pro-reitoria Pesquisa Pos-graduacao, 2019)
The density and distribution of soybean plants can interfere in the plant growth stage and yield, as well as phytosanitary management of this crop. Thus, innovations in production systems must be followed by improvements in pesticide application technology. Therefore, this study aimed to evaluate the influence of soybean sowing arrangements on fungicide application technology, with or without air assistance in the spray boom, using qualitative and quantitative assessments of the spray deposits. In the experiments, a randomized block design with split plots was used. Four soybean sowing arrangements: Conventional (CO), Double row (DR), Narrow row (NR), and Crossed rows (CR) composed the main plots, and fungicide application technologies with air assistance (AA) and without air assistance (WA) in the spray boom composed the subplots, with four replications. For the assessment of spray deposits, Brilliant Blue tracer dye was used in the spray solution, and the spray coverage was evaluated using water-sensitive papers. The effects of different soybean sowing arrangements on deposits and spray coverage were limited. However, an increase in spray deposits on the lower part of the soybean plants was observed with air assistance in the spray boom.
Keywords: Glycine max; distribution of plants; air sleeve boom sprayer